THE EFFECT OF SERVANT LEADERSHIP, EMOTIONAL INTELLIGENCE, AND PURPOSE IN LIFE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN XYZ EARLY CHILDHOOD YEARS – ELEMENTARY - Novia Purnomo; Khoe Yao Tung (Universitas Pelita Harapan, 2022)
To prepare the students with the demand of life in the future, teachers must continuously develop mastery of new knowledge, skills, competencies, and aptitudes. Education has entered a period of profound disruptive transition. It requires teachers to have organizational citizenship behavior (OCB). The purpose of this quantitative study is to examine the effect of servant leadership, emotional intelligence, and purpose in life on organizational citizenship behavior in XYZ Early Childhood Years and Elementary School. Fifty-five teachers of XYZ Early Childhood Years and Elementary School completed the online questionnaires. Path analysis through PLS SEM method is employed to test the proposed hypotheses. The results showed that servant leadership has positive effect on purpose in life and organizational citizenship behavior. It was found that emotional intelligence has positive effect on purpose in life. Purpose in life also has positive effect on organizational citizenship behavior. In contrast, it was found that emotional intelligence does not have positive effect on organizational citizenship behavior.Bahasa Indonesia Abstrak: Siswa perlu dipersiapkan untuk menghadapi tuntutan kehidupan masa mendatang, guru harus terus mengembangkan penguasaan pengetahuan, keterampilan, kompetensi, dan bakat baru. Pendidikan telah memasuki masa transisi yang penuh disrupsi. Hal ini menuntut guru untuk memiliki organizational citizenship behavior (OCB). Tujuan dari penelitian kuantitatif ini adalah untuk menguji pengaruh servant leadership, emotional intelligence dan purpose in life terhadap organizational citizenship behavior di TK-SD XYZ. Lima puluh lima guru TK dan SD XYZ menyelesaikan kuesioner online. Perhitungan penelitian menggunakan analisis jalur melalui metode Partial Least Square-Structural Equation Modeling (PLS SEM) digunakan untuk menguji hipotesis yang diajukan. Hasil penelitian menunjukkan bahwa servant leadership berpengaruh positif terhadap organizational citizenship behavior. Ditemukan juga bahwa servant leadership berpengaruh positif terhadap purpose in life dan emotional intelligence berpengaruh positif terhadap purpose in life. Purpose in life juga berpengaruh positif terhadap organizational citizenship behavior. Sebaliknya, emotional intelligence tidak berpengaruh positif terhadap organizational citizenship behavior.